Neuroprotection in radiotherapy of brain metastases: a pattern-of-care analysis in Germany, Austria and Switzerland by the German Society for radiation Oncology : Working Group Neuro-Radio-Oncology (DEGRO AG-NRO) - Gleim, Nils; Rühle, A.; Heider, S.; Nägler, F.; Giordano, Frank Anton; Combs, Stephanie; Becker, J.; Niyazi, M.; Grosu, Anca-Ligia; Nicolay, Nils; Seidel, Clemens (Clinical and translational radiation oncology, 2024)
Background and purpose - Many patients with solid tumors develop brain metastases (BM). With more patients surviving long-term, preservation of neurocognitive function gains importance. In recent years, several methods to delay cognitive deterioration have been tested in clinical trials. However, knowledge on the extent to which these neuroprotective strategies have been implemented in clinical practice is missing. - Materials and methods - We performed an online survey regarding treatment patterns of BM in German-speaking countries, focused on the use of neuroprotective approaches. The survey was distributed among radiation oncologists (ROs) registered within the database of the German Society for Radiation Oncology (DEGRO). - Results - Physicians of 78 centers participated in the survey. Whole brain radiotherapy (WBRT) is still preferred by 70 % of ROs over stereotactic radiotherapy (SRT) in patients with 6-10 BM. For 4-5 BM WBRT is preferred by 23 % of ROs. The fraction of ROs using hippocampal sparing (HS) in WBRT has increased to 89 %, although the technique is used on a regular basis only by a minority (26 %). The drug memantine is not widely prescribed (14% of ROs). A trend was observed for university hospitals to implement neuroprotective approaches more frequently. - Conclusion - There is considerable heterogeneity regarding the treatment of BM in German-speaking countries and a general standard of care is lacking. Neuroprotective strategies are not yet standard approaches in daily clinical routine, although usage is increasing. Further clinical trials, as well as improvement of technical opportunities and reimbursement, might further shift the treatment landscape towards neuroprotective radiation treatments in the future.
Gesehen am 29.01.2025